2018
DOI: 10.1080/19396368.2018.1467512
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS1 and ADAMTS5 metalloproteases produced by Sertoli cells: a potential diagnostic marker in azoospermia

Abstract: ADAM: A Disintegrin and Metalloproteinase; ADAMTS1 and ADAMTS5: A Disintegrin and Metalloproteinase with 10 Thrombospondin Motifs 1 and 5; ADAMTS: A Disintegrin and Metalloproteinase with Thrombospondin; ABP: androgen binding protein; CAMs: cell adhesion molecules; ECM: extracellular matrix; FSH: follicle stimulating hormone; FSHR: FSH receptors; HRP: horseradish peroxidase; MMP: matrix metalloproteinases; MP: metalloproteinases; NOA: nonobstructive azoospermia; OA: obstructive azoospermia; TIMP-1: tissue inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…ADAMTS5 protein expression in semen was significantly related with sperm production. [25] When compared with fertile control group, Aydos et al [26] have revealed the expression of ADAMTS5 was statistically significant lower in nonobstructive azoospermia. Researchers thought low ADAMTS expression might have an important role in the etiology of male infertility and might use as a predictive marker for azoospermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS5 protein expression in semen was significantly related with sperm production. [25] When compared with fertile control group, Aydos et al [26] have revealed the expression of ADAMTS5 was statistically significant lower in nonobstructive azoospermia. Researchers thought low ADAMTS expression might have an important role in the etiology of male infertility and might use as a predictive marker for azoospermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted protein contents were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis and then transferred onto polyvinylidene difluoride membranes. Afterward, the membrane was blocked with 5% StartingBlock Blocking Buffer (Thermo Scientific, Pittsburgh, PA, USA) for 24 h. When the blocking step was terminated, the membrane was incubated with the primary antibodies against anti-SF-1 (1:1000; Santa Cruz Biotechnology, Inc., Santa Cruz, California, USA), LHCGR (diluted at 1:500; Pro-teinTech, USA), FSHR (1:1000; Abcam, Cambridge, UK), and GAPDH (1:25,000; Abcam) at 4 C 21-23 for 24 h. The membrane was rinsed in phosphate-buffered saline (PBS)-Tween (005% Tween in PBS) three times (each time 5 min) and probed with horseradish peroxidase-conjugated antigoat or antirabbit secondary antibody (immunoglobulin G, diluted at 1:5000; Abcam) at room temperature for 1 h. 21 Finally, the protein bands were visualized using the enhanced chemiluminescence reagent kit (ECL-Plus; GE Healthcare), according to the manufacturer's instructions.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTSs), which belong to the M12 metallopeptidase family, are responsible for the migration of differentiated germ cells through the seminiferous tubule wall by organizing the degradation and reformation of the ECM [ 31 ]. In fact, we recently demonstrated that ADAMTS1 and ADAMTS5 protein levels expressed in Sertoli cells were decreased approximately 2-fold in cases of NOA [ 32 ]. The effect of enzymatic digestion on the success of sperm retrieval in cases where these proteases are defective is a subject of further research.…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsimentioning
confidence: 99%